Physicochemical Characterization of Kefir Combination from Goat Milk and Almond Milk - Rini Hardiyanti; Muhammad Taufik; Alensia Estetika Manalu; Elsa Priskila; May Rifani Br Ginting; Zabdan Ahmad Arrazi (Talenta Publisher, 2025)
Kefir is a fermented milk that contains probiotic bacteria. It is made by adding kefir grain starter as a source of lactic acid bacteria. The combination of goat milk and almond milk, along with the addition of pineapple core extract, is an effort to enhance the nutritional value of probiotic kefir milk. The aim of this study is to determine the quality characteristics of the combined kefir made from almond milk and goat milk with varying milk ratios (30:70, 40:60, and 50:50%) and the effect of pineapple core extract on the combined kefir. The combination is expected to produce kefir with unique characetristics due to the nutritional differences between animal-based and plant-based milk. Quality characteristics include pH testing measured using a pH meter, viscosity testing using a Brookfield viscometer, titratable acidity (total acid) using an alkalimetric titration method, and protein content tested using the Kjeldahl method. The results obtained show that the combined kefir made from goat milk and almond milk with the addition of pineapple core extract affects the pH, viscosity, titratable acidity, and protein content. The optimal variation was obtained at a 40:60% ratio, with a pH of 3.7650 ± 0.0849, viscosity of 0.7410 ± 0.0283, titratable acidity (%) of 1.2043 ± 0.0636, and protein content of 1.3509% ± 0.0304.